Shaping the niche: lessons from the Drosophila testis and other model systems - Papagiannouli, Fani; Lohmann, Ingrid (Biotechnology journal, 2012)
Stem cells are fascinating, as they supply the cells that construct our adult bodies and replenish, as we age, worn out, damaged, and diseased tissues. Stem cell regulation relies on intrinsic signals but also on inputs emanating from the neighbouring niche. The Drosophila testis provides an excellent system for studying such processes. Although recent advances have uncovered several signalling, cytoskeletal and other factors affecting niche homeostasis and testis differentiation, many aspects of niche regulation and maintenance remain unsolved. In this review, we discuss aspects of niche establishment and integrity not yet fully understood and we compare it to the current knowledge in other model systems such as vertebrates and plants. We also address specific questions on stem cell maintenance and niche regulation in the Drosophila testis under the control of Hox genes. Finally, we provide insights on the striking functional conservation of homologous genes in plants and animals and their respective stem cell niches. Elucidating conserved mechanisms of stem cell control in both lineages could reveal the importance underlying this conservation and justify the evolutionary pressure to adapt homologous molecules for performing the same task.